Rancang Bangun Prototype Sistem Penyiraman Otomatis pada Tanaman Anggrek Berbasis ESP32 dan Sensor Ultrasonic - Silvi Diah Fitriani; Fahmi Fachri (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2026)
Orchids are ornamental plants that require stable humidity conditions to support optimal growth. However, manual watering methods tend to be inefficient, prone to errors such as overwatering and underwatering, and unable to monitor water availability in real time. This study aims to design and develop a prototype of an automatic watering system based on the ESP32 microcontroller, integrated with a soil moisture sensor and an ultrasonic sensor. The method used is Research and Development (R&D) following the ADDIE model, which includes the analysis, design, development, implementation, and evaluation stages. The system operates by reading real-time soil moisture and water level values, then processing the data using the ESP32 to control the water pump based on threshold values, where the pump activates when soil moisture is below 30% and stops when moisture is above 60%. Additionally, a buzzer is used as a warning indicator; the buzzer sounds when the water level is below 5 cm and stops when the water level is above 50 cm. The research results show that the system is capable of adapting to changes in environmental conditions, where watering frequency increases under hot conditions, while soil moisture remains more stable under cool conditions. Overall, the developed system is capable of improving efficiency, accuracy, and reliability in the orchid watering process while reducing reliance on manual methods.